Effects of Lithium Bis(fluorosulfonyl)imide Concentration on Performances of Lithium-ion Batteries Containing Sulfolane-based Electrolytes. Issue 11 (24th July 2020) - Hirata, Kazuhisa; Morita, Yoshihiro; Kawase, Takeo; Sumida, Yasutaka
Abstract : Carbonate-free electrolytes based on lithium bis(fluorosulfonyl)imide (LiFSI) and sulfolane (SL) (LiFSI/SL) are promising alternatives to conventional electrolytes based on lithium hexafluorophosphate and ethylene carbonate. In this study, we show the effects of LiFSI concentration on performances of LiCoO2 /graphite full cells with LiFSI/SL (1–2.25 mol dm −3 ). The LiFSI/SL electrolytes behave as ideal Walden electrolytes. Cells containing LiFSI/SL with various concentrations exhibit excellent cycle stabilities regardless of their concentrations though they have free-state solvent molecules. Furthermore, the cells containing LiFSI/SL with higher LiFSI concentrations show superior high-rate performances with high discharge capacities and discharge voltages due to high lithium dissociation and lithium ion transference number. The cell containing 1.5 mol dm −3 LiFSI/SL specifically shows excellent low-temperature performance with high discharge capacity and discharge voltage. The low-temperature performance is ascribed from non-crystallinity of the electrolyte as well as the high lithium dissociation.